Energy System Planning towards Renewable Power System: Energy Matrix Change in Cuba by 2030 - L. Vazquez; Y. Majanne; M. Castro; J. Luukkanen; O. Hohmeyer; M. Vilaragut; D. Diaz (ELSEVIER SCIENCE BV, 2025)
Since 2013, the biggest Caribbean island, Cuba, has been undertaking an energy matrix change. There is a strong political intention to replace fossil fuels by renewable energy and improve efficiency and security of the national energy system. By 2030, 24% of electric power shall be produced from renewable sources. Transition from centralized fossil fuel fired power system towards distributed renewable generation based system requires changes to conventional energy planning and system design procedures as well as physical structures of the national energy system. This paper introduces three analysis axis: Scenario building for future supply-demand balance, scenario for a 100% renewable energy system for Cuba, and a roadmap from existing power system to the system with high share of distributed renewable generation. This work is a part of European Union funded Erasmus+ project "Capacity Building for Renewable Energy Planning in Cuban Higher Education Institutions", CRECE.